Learning Robotics using Python : Design, simulate, program, and prototype an autonomous mobile robot using ROS, OpenCV, PCL, and Python, 2nd Edition /: Design, simulate, program, and prototype an autonomous mobile robot using ROS, OpenCV, PCL, and Python, 2nd Edition. (2018) - Joseph, Lentin
No abstract available